THE EFFECT OF QUICK WRITE STRATEGY ON STUDENTS’ ABILITY IN WRITING EXPOSITION TEXT - Gazela,, Aldera L.; Suhami (Indonesian Journal of Studies on Humanities, Social Sciences and Education, 2024)
Good writing skills are very important for students in facing academic challenges. However, students often have difficulty in writing exposition texts well. This study examines the effect of a speed writing strategy on students' writing ability in the context of analytical exposition texts. The type of research is experimental. The population in this study were all students of SMA Negeri 3 Sungai Penuh, and the samples were the control class (XI IPS 2) and the experimental class (XI IPA 1) determined by random sampling technique. data was collected by a test on exposition text writing skills. The results showed that the control class did not show significant improvement in their writing skills, as the average scores on both tests fell into the "less good" category. However, the experimental class showed significant improvement, with the average post-test score categorized as "excellent". The t-test analysis showed the calculated t value (12.146) > the critical t value (1.713) at the 0.05 significance level. These results indicate that the rapid writing strategy had a positive and significant impact on students in the experimental class, improving their ability to write analytical exposition texts, thus the importance of using effective teaching methods in improving students' writing ability.